Evolution of the hectocotylus in Sepiolinae (Cephalopoda: Sepiolidae) and description of four new genera - BELLO, Giambattista (European Journal of Taxonomy, 2020)
The subfamily Sepiolinae (Mollusca: Cephalopoda: Sepiolidae), currently containing the genera Sepiola Leach, 1817, Euprymna Steenstrup, 1887, Inioteuthis Verrill, 1881, Rondeletiola Naef, 1921 and Sepietta Naef, 1912, is characterized by the hectocotylization of the left dorsal arm, i.e., its transformation into a copulatory organ thanks to modifications of sucker/pedicel elements. The hectocotylus morphology varies to a great extent across genera and species. In particular, one to several pedicels in its proximal third lose their sucker and become highly and diversely modified in shape to constitute a copulatory apparatus. An evolutionary gradient was observed in the copulatory apparatus morphology, from the simple modification into a papilla of just one pedicel from the third element of the ventral sucker row (some nominal species of Euprymna) to a quite complex structure involving several variously modified pedicels from both the ventral and dorsal sucker rows (Inioteuthis). In some species, elements in the distal portion of the hectocotylus may also be highly modified, such as the columnar suckers in Euprymna. The hectocotylian diversity allows to distinguish nine groups of species that do not match the current generic subdivision of Sepiolinae. Additional morphological characters (number of sucker rows on arms, female bursa copulatrix, occurrence and shape of visceral light organs, etc.) corroborate the subdivision of Sepiolinae into nine subtaxa, i.e., genera. Accordingly, a cladogram is drawn to describe the possible phylogenetic relationships among the nine clades. To comply with these results, all current genera are redefined and four new genera are described, namely Adinaefiola gen. nov., Boletzkyola gen. nov., Eumandya gen. nov. and Lusepiola gen. nov.